Clinical Correlates of Cannabis Use Among Individuals With Attention Deficit Hyperactivity Disorder. Issue 9 (September 2018) - Brandt, Ariel; Rehm, Jürgen; Lev-Ran, Shaul
Abstract : Abstract: In this study, we explored patterns and clinical correlates of cannabis use among individuals with attention-deficit/hyperactivity disorder (ADHD). Data were obtained from Wave 2 of the National Epidemiologic Survey on Alcohol and Related Conditions (2004–2005). Psychiatric disorders were assessed using the Alcohol Use Disorder and Associated Disabilities Interview Schedule. We used multivariate logistic regression models adjusting for sociodemographics, psychiatric disorders, and substance use disorders. Prevalence of cannabis use among individuals with and without ADHD was 14.3% and 4.3%, respectively. Diagnosis of any psychiatric disorder was significantly higher among those with ADHD and concurrent cannabis use compared with nonusers (adjusted odds ratio [AOR], 2.8; 95% confidence interval [CI], 1.08–6.41), as were odds of a lifetime personality disorder (AOR, 4.04; 95% CI, 1.84–8.84). Individuals with the hyperactive subtype initiated cannabis at a significantly earlier age compared with those with the inattentive subtype (13.8 ± 0.56 vs . 16.3 ± 0.5 years, respectively; p = 0.0017). Longitudinal prospective studies are required to further clarify the effects and patterns of cannabis use in this clinical population.